Proceedings of the 2nd International Conference on Intervention and Applied Psychology (ICIAP 2018) 2019
DOI: 10.2991/iciap-18.2019.50
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Attitudes Toward Inclusive Education

Abstract: Implementing inclusive education requires not only facilities and physical support but also human resources, in this case pre-service teachers. Pre-service teachers, who come from different educational backgrounds, are one of the most important components in implementing inclusive education due to their interactions with special needs children. This study aims to compare the attitudes of pre-service teachers toward inclusive education based on experiences of direct interaction, training, and teaching special n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(16 reference statements)
0
8
1
Order By: Relevance
“…According to other research, study programme is another variable that can influence pre‐service teachers' attitudes towards inclusion (e.g. AlMahdi & Bukamal, 2019; Muwana & Ostrosky, 2014; Qandhi & Kurniawati, 2019; Subban & Mahlo, 2017). For example, Woodcock's (2011) study found that pre‐service teachers from the primary programme had more positive attitudes than their counterparts from the pre‐school programme.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to other research, study programme is another variable that can influence pre‐service teachers' attitudes towards inclusion (e.g. AlMahdi & Bukamal, 2019; Muwana & Ostrosky, 2014; Qandhi & Kurniawati, 2019; Subban & Mahlo, 2017). For example, Woodcock's (2011) study found that pre‐service teachers from the primary programme had more positive attitudes than their counterparts from the pre‐school programme.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ismailos et al (2019), one of the main goals of teacher training programmes today is to prepare trainees for classroom diversity, so it is important that these programmes prepare pre‐service teachers in theoretical, pedagogical and practical terms, influencing the formation of beliefs and then actions. Based on research, authentic practices and situations in shared settings with students with disabilities are considered to be one of the most influential factors shaping pre‐service teachers' attitudes (Avramidis & Norwich, 2002; Beacham & Rouse, 2012; Forlin et al, 2010; Qandhi & Kurniawati, 2019). Muwana and Ostrosky (2014) suggested that the 90% of pre‐service teachers who had contact with people with special needs had significantly more positive attitudes than those who had no contact, and this contact may be the reason why their attitudes were positive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of some recent studies show that in the context of inclusion, physical problems such as class sizes and materials are experienced in schools and teacher attitudes depend on teachers' experiences and professional competencies (Moberg et al, 2020;Nadia, 2012;Qandhi & Kurniawati, 2019).…”
Section: Related Researchmentioning
confidence: 99%